Smart gold nanosensor for easy sensing of lead and copper ions in solution and using paper strips1. Issue 84 (16th September 2015) - Nath, Peuli; Arun, Ravi Kumar; Chanda, Nripen
<x xml:space="preserve">Abstract</x> A smart gold nanosensor, Au–TA–DNS is designed that can rapidly detect very low concentrations of Pb2+ and Cu2+ ions.